131 Diagnosis of arrhythmogenic cardiomyopathy and overlap with cardiac adaptation to exercise: insights from a cardiac magnetic resonance study. (May 2019) - Finocchiaro, Gherardo; Moccia, Eleonora; Papatheodorou, Stathis; Miles, Chris; Zaidi, Abbas; Behr, Elijah; Bunce, Nicholas; Anderson, Lisa; Sharma, Sanjay; Merghani, Ahmed; Papadakis, Michael
Abstract : Background: The diagnosis of arrhythmogenic right ventricular cardiomyopathy (ARVC) is often challenging and structural abnormalities typical of the disease may overlap with changes reflective of cardiac adaptation to exercise. The aim of the study was to assess the performance of the cardiac magnetic resonance (CMR) 2010 Task Force Criteria (TFC) in a cohort of patients with definite diagnosis of ARVC and define the overlap with a cohort of highly trained athletes of similar age and sex. Methods: We compared the CMR features of 43 patients (mean age 49±17 years, 49% males, 32 (74%) genotyped) with a definite diagnosis of ARVC according to the revised TFC to 97 (mean age 45±16 years, 61% males) highly-trained athletes of similar age and sex, where cardiac disease was excluded after comprehensive work-up. Results: The CMR was abnormal in 37 (86%) patients. The RV was affected in isolation in 17 (39%) patients, with 18 (42%) patients exhibiting biventricular involvement and 2 (5%) patients showing isolated left ventricular involvement. The most common RV abnormalities were regional wall motion abnormalities (RWMA) (n=34; 79%), RV dilatation fulfilling a major or minor volume TFC (n=18; 42%), impaired systolic function (RVEF ≤45%: n=17; 40%) and myocardial fibrosis (n=13; 30%). The predominant LV abnormality was myocardial fibrosis (n=20; 47%), with a small proportion of patients exhibiting RWMA (n=6; 14%) and impaired systolic function (LVEF <50%: n=6; 14%). Twenty-three (53%) patients fulfilled a major (n=14; 32%) or a minor (n=9; 21%) CMR TFC. Sixteen (16%) athletes exceeded the cut-off values for RV volumes used as a major (n=10; 10%) or a minor (n=6; 6%) TFC with an inverse relationship between age and RV volumes (r=-0.41, p=0.001). None of the athletes fulfilled the TFC for RV ejection fraction. Applying the CMR TFC to the ARVC patient population, showed a sensitivity of 33% for the major and 28% for the minor criteria. Applying the RV volume and systolic function TFC values in the entire study population, showed a sensitivity of 53%, a specificity between 83% and an accuracy of 0.68. Please see (Figure 1 ). Conclusion: The great majority (86%) of patients with ARVC demonstrate structural abnormalities suggestive of cardiomyopathy on CMR but only 53% fulfil any of the CMR TFC. A small proportion (16%) of older athletes demonstrate significant RV dilatation that overlaps with the volume criteria for ARVC. The emergence of ARVC as a biventricular disease provides an opportunity to re-evaluate the diagnostic criteria and include LV involvement in conjunction with RV involvement to improve diagnostic accuracy. Conflict of Interest: no